(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyses state regulation and business support in conditions of macroeconomic instability. Four types of risks are identified: financial-resource, regulatory-operational, market-technological, and reputational-institutional. The key challenges are outlined, and solutions are proposed, including digitalisation of interactions, tax incentives, public-private partnerships (PPP), and greater transparency in fund allocation.